Preparation of PTFE-reinforced anion exchange membranes using poly (vinyl benzyl chloride-co-vinyl imidazole) functionalized with 1, 2-dime-thyl-imidazole and their electrochemical properties for water electrolysis - Eo, Jae Young; Lee, Tae Kyung; Kim, Gyungsoo; Park, Bo Ryoung; Chai, Geun Seok; Yoo, Sung Jong; Kim, Jong Hak; Kim, Jeong-Hoon (Elsevier BV, 2025)
In recent decades, anion exchange membrane water electrolysis technology has witnessed significant advancements, facilitating the development of high-performance anion exchange membranes. As critical components of membrane electrode assemblies, anion exchange membranes require appropriate mechanical properties, high ionic conductivity, and excellent alkaline durability, and low preparation cost. This study presents innovative aryl-ether free anion exchange membranes fabricated by pore-filling 4-vinyl benzyl chloride and 1-vinylimida-zole monomers into porous PTFE substrates, using benzoyl peroxide as an initiator. The substrate thickness was varied (20, 50, and 100 mu m). Free radical thermal polymerization of 4-vinyl benzyl chloride and 1-vinylimi-dazole within the porous PTFE substrate was followed by functionalized with dimethyl imidazole to incorporate imidazolium functional groups. The physicochemical and electrochemical properties of the membranes were evaluated across varying monomer ratios and substrate thicknesses for their applicability in anion exchange membrane water electrolysis. The optimized membrane with a 100-mu m PTFE substrate membrane exhibited excellent cell performance, achieving 2.4 A/cm2 at 2.0 V in a single-cell water electrolysis test (1 M KOH solution at 80 degrees C). This study could provide the valuable insights in developing PTFE reinforced composite membranes in AEMWEs.